Protecting your library's digital sources : the essential guide to planning and preservation - Kahn, Miriam (Miriam B.) (American Library Association, 2004)
Preservation and disaster expert Kahn brings clear guidance and practical expertise to address libraries' worst-case disaster before they happen. Library directors and managers responsible for creating disaster plans as well as those in computer services and information technology departments will benefit from this comprehensive guide.